PELUKAAN BENIH DAN PERENDAMAN DENGAN ATONIK PADA PERKECAMBAHAN BENIH DAN PERTUMBUHAN TANAMAN SEMANGKA NON BIJI (Citrullus vulgaris Schard L.) - Novianti Sunarlim; Syukria Ikhsan Zam; Joko Purwanto (Jurnal Agroteknologi, 2012)
Research was conducted from August until October 2011 at Agronomy Laboratory and research farm of Agriculture and Animal Science Faculty of State Islamic University Sultan Syaif Kasim Riau. Triploid watermelon of F1 Riendow was used in this experiment. The experimental design used was Completely Randomized Design arranged in factorial between alteration seed coats (with and without clipping the seed coat) and 4 different times of soaking with Atonik (0, 30,60 and 90 minutes) with 3 replications for germination experiment and soaking with Atonik (0, 30, 60 dan 90 minutes) with 6 replications for plant growth experiment. The research was conducted in the pot with peat soil. Result of the research showed that seed germination with clipping the seed coat (64.54%) was higher than without clipping the seed coat (38.28%). There was no interaction between alteration of the seed and soaking time. Soaking time with Atonik did not affect seed germination and also the growth of the plants (stem length, number of leaves, plant and root dry weight) at 55 days after planting.